1996
DOI: 10.1046/j.1460-9592.1996.d01-21.x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative complications in children undergoing selective posterior rhizotomy: a review of 105 cases

Abstract: Medical histories for 105 consecutive children who underwent selective posterior rhizotomy (SPR) were reviewed to determine the incidence and clinical significance of adverse events related to anaesthesia and surgery. No intraoperative or postoperative events with potential for lasting morbidity, nor life threatening events, were identified. Intraoperatively, the most common adverse events were moderate elevation of body temperature (13/105) and transient dysrhythmias (8/105). The most frequent postoperative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 2 publications
2
6
1
1
Order By: Relevance
“…In both cases it was readily treated and did not prolong hospitalization. Bronchospasm was noted in 1 patient (0.6%), an incidence similar to that reported by Van de Wiele et al [18]. In contrast, Abbott et al [20] reported much higher rates of these respiratory complications until special precautions were taken.…”
Section: Intraoperative Complicationssupporting
confidence: 73%
See 2 more Smart Citations
“…In both cases it was readily treated and did not prolong hospitalization. Bronchospasm was noted in 1 patient (0.6%), an incidence similar to that reported by Van de Wiele et al [18]. In contrast, Abbott et al [20] reported much higher rates of these respiratory complications until special precautions were taken.…”
Section: Intraoperative Complicationssupporting
confidence: 73%
“…Urinary tract infections (0.6%) were unusual despite the almost universal use of an indwelling catheter, and were less common in this study than reported elsewhere [18]. Balanitis occurred in 2 male children, in whom the foreskin was not pulled forward after intraoperative catheterization.…”
Section: Perioperative Complicationscontrasting
confidence: 46%
See 1 more Smart Citation
“…In comparison, no significant complications were noted in a series of 105 cases [61]. Sensory loss and transient hyperesthesias are often seen after selective posterior rhizotomy, but can be minimized when the percentage of nerve rootlets sectioned is kept to a minimum.…”
Section: Complications Of Rhizotomymentioning
confidence: 99%
“…In our study, we found that between 487 and 542 operations are performed per year by the 36 centers included. Van de Wiele et al [23 ]treated 105 children suffering from spasticity with SDR between 1986 and 1991. Park [2] operated 681 patients with spastic diplegia and quadriplegia between 1989 and 1999.…”
Section: Discussionmentioning
confidence: 99%